Comparative Study of Growth, Carcass Characteristics and Economics of Crossbred, Indigenous and Exotic Pigs - Ramakrishnan S (Department of Livestock Production Management, College of Veterinary and Animal Sciences, 2001)
A detailed investigation was carried out to compare the merits and demerits of crossbred pigs over indigenous and exotic pigs with respect to growth and carcass characteristics and to study the economic feasibility of rearing crossbred pigs. Three groups of twelve weaned female piglings each belonging to indigenous (Desi), Large White Yorkshire (LWY) and crossbred (CB) (LWY x Desi) of Centre for Pig Production and Research, Mannuthy were selected as uniform as possible with regard to age and body weight. Animals in each breed group were randomly divided into two equal dietary treatment groups of six. Treatment group one was fed with a ration specified by ICAR and treatment group two with a ration containing 10 per cent less crude protein than ICAR ration. All the pigs were fed isocaloric ration as per ICAR recommendation. The protein level in the ration had a moderate influence on the performance of grower pigs. There was a trend in favour of full rCAR ration with respect to the parameters like growth rate, feed conversion efficiency, average daily weight gain and carcass characteristics.